Efektivitas Pertanggung Jawaban Notaris dalam Penyusunan Akta Autentik Berkaitan dengan Perjanjian Perkawinan - Az Zahra, Salsabila Qalwiah; Hartati, Endah (UNES Law Review, 2023)
Nowadays there is unclear norm (Vague of norms) in some domains of rules in marriage agreements in the Marriage Law, where a marriage legal unit in Indonesia should be drawn up which is related to the marriage agreement referring to Article 29. The provisions in Article 29 of the Marriage Law do not have clear reasons related the entire marriage agreement, for example it requires aspects and there are no things contained in the marriage agreement, the legalization of the marriage agreement and related to the mechanism of change so that there can be a guarantee that the change will not harm the other party. Regarding the type of normative juridical research, it leads to the object of research, including legal issues which relate to the responsibility of a Notary in the preparation of an Authentic Deed in a Marriage Agreement. So that the results of this research are authentic deeds which include the strongest written evidence and the full meaning where the Judge does not have to explore other aspects of truth unless it is contained in the notary deed. In addition, marriage agreements can be drawn up through the wishes of the prospective bride and groom where there is no contradiction in the Constitution of the Republic of Indonesia, there are no violations of religious law or aspects of morality. This situation is in harmony with the principle of freedom of contract.